Industrial development in a border area: facts and figures from East London - Barker, John Percy (Rhodes University, Faculty of Commerce, Department of Economics, 2026)
In the early 1950's the area of the eastern Cape Province adjoining the Transkei was the object of an intensive study known as the Border Regional Survey and five volumes have already been published. This work is a more detailed investigation of one aspect of the economy, namely the growth of manufacturing industry. Its importance lies in the fact that not only is the African population increasing rapidly, but that effective rehabilitation of peasant farming in the Transkei and Ciskei must necessarily displace large numbers from the land. Expansion of manufacturing industry would appear to be the most effective means of providing remunerative employment for these people. Moreover, the government has embarked upon a policy of encouraging the establishment of factories on the periphery of the Bantu areas, and the eastern Cape is an important area in this general scheme. It may well be the most crucial testing point of the whole policy of 'border industries', because with its large Transkeian hinterland it is the area most in need of expanding employment opportunities
Keywords: Industrialization; East London (South Africa) -- Industries